Autonomous Motivation and Pro-Environmental Behaviours Among Bedouin Students in Israel: A Self-Determination Theory Perspective. (26th October 2015) - Kaplan, Haya; Madjar, Nir
Abstract: Promoting pro-environmental behaviours (PEBs) among students is a major concern for educators. The present article presents an educational program based on a self-determination theory framework (SDT; Deci & Ryan, 2000 ) and a study demonstrating that working according to the theoretical principles presented in the program leads to the desired outcomes. The primary aim of the study was to test whether a hypothesised model in which autonomy support by students' parents and moderators in a large-scale intervention program would be associated with autonomous motivation, which would in turn lead to PEBs, over and above the contributions of the students' self-perceived competence and relatedness. The participants were 102 Bedouin high-school students (Grades 8 to 10) sampled from a cultural background characterised by a collectivist-hierarchical society in Israel. The results, based on structural equation modelling, indicated that moderators and parental autonomy support, as well as self-perceived relatedness and competence, were associated with students' autonomous motivation, which in turn was associated with pro-environmental behaviours (including cleaning behaviours, activism, and preserving behaviours). The study supported the hypothesised model and demonstrated that SDT can be utilised as a theoretical framework for educational programs aimed at improving students' self-determined PEBs.